Burden of Menstrual Pain Measured by Heatmap Visualization of Daily Patient-Reported Data in Japanese Patients Treated with Ethinylestradiol/Drospirenone: A Randomized Controlled Study - Momoeda M; Akiyama S; Yamamoto S; Kondo M; Fukai T (Dove Medical Press, 2020)
Mikio Momoeda,1 Sayako Akiyama,2 Shigetomo Yamamoto,3 Masami Kondo,4 Takeshi Fukai4 1Department of Integrated Women’s Health, St Luke’s International Hospital, Tokyo, Japan; 2Market Access, Bayer Yakuhin Ltd., Tokyo, Japan; 3Medical Affairs, Bayer Yakuhin Ltd., Osaka, Japan; 4Product Development, Bayer Yakuhin Ltd., Osaka, JapanCorrespondence: Mikio Momoeda 9-1 Akashicho, Chuo-ku, Tokyo 104-8560, JapanTel +81-3-3541-5151Fax +81-3-5550-2605Email momoeda-tky@umin.ac.jpPurpose: Dysmenorrhea negatively affects women’s quality of life and poses a considerable economic burden. A recent study in Japanese patients with dysmenorrhea (NCT01892904) reported a significant reduction in the number of days with menstrual pain after treatment with a flexible extended regimen of ethinylestradiol (EE)/drospirenone (DRSP) compared with a cyclic regimen. However, individual patients’ menstrual pain patterns and intensities were not indicated. Heatmapping was used to visualize menstrual pain patterns and intensities by re-evaluating the previously published data from NCT01892904.Patients and Methods: NCT01892904 was a Phase III, multicenter, randomized, open-label, active-control study of 212 women aged ≥ 20 years randomized 1:1 to receive flexible extended or 28-day cyclic EE/DRSP treatment. Daily pain levels were recorded in patient diaries, and menstrual pain patterns and intensities were visualized using heatmapping. Patients were stratified by baseline dysmenorrhea scores and primary or secondary dysmenorrhea.Results: The heatmap data demonstrated that EE/DRSP reduced the degree of menstrual pain. Regular peaks of menstrual pain were alleviated in the extended regimen group but were still observed in the cyclic regimen group. While a decrease in the days with menstrual pain was observed in patients with higher baseline dysmenorrhea scores (5– 6), those with lower baseline scores (3– 4) were more likely to experience lower intensities of menstrual pain. Although pain relief was less likely in patients with secondary dysmenorrhea, those who had lower baseline dysmenorrhea scores (3– 4) and received the flexible extended regimen experienced a greater reduction in the number of days with menstrual pain than those who received the cyclic regimen.Conclusion: Heatmapping effectively visualized the daily burden of menstrual pain in Japanese patients with dysmenorrhea. The analysis using heatmaps suggested that the flexible extended EE/DRSP treatment regimen was more likely to alleviate the regular occurrence of menstrual pain peaks compared with the cyclic regimen.Keywords: dysmenorrhea, ethinylestradiol, pain measurement, patient-reported outcomes